Saccharomyces carlsbergensis fdp mutant and futile cycling of fructose 6-phosphate. - Bañuelos, M (1982)
In Saccharomyces, the addition of glucose to cells grown in media lacking sugars causes irreversible inactivation of fructose bisphosphatase. One function of this process might be to prevent a futile cycle of formation and hydrolysis of fructose 1,6-bisphosphate. We tested such cycling by assessing the labeling of the 1-position of glucose in polysaccharides from [6-14C]glucose (J.P. Chambost and D. G. Fraenkel, J. Biol. Chem. 225:2867-2869, 1980) by using mutants impaired in glucose growth and known not to inactivate the phosphatase normally (i.e., the fdp mutant of Saccharomyces carlsbergensis [van de Poll et al., J. Bacteriol. 117:965-970, 1974] and the similar cif mutant of Saccharomyces cerevisiae [Navon et al., Biochemistry 18:4487-4499, 1979] ), as well as in the wild-type strain tested in the 1-h period before inactivation is complete. There was marginal, if any, cycling in any situation, and we conclude that the phosphatase activity is controlled by means other than inactivation or that the extent of cycling is too low to be significant, or both. For the fdp mutant data are also presented on growth, rate of glucose metabolism, metabolite accumulations, enzyme levels, and glucose transport, but the primary lesion is unknown.